Comparison of the Effects of Transformational Leadership Style on Performance with Mediation of Pamong Motivation of Caturtunggal and Condongcatur Villages, Kapanewon Depok, Sleman Regency - Apriliani Apriliani; Arief Subyantoro; Hendro Widjanarko (Journal of Business Innovation and Research, 2022)
This research aims to examine the effect of transformational leadership style on employee performance, to examine the effect of mediating motivation on the relationship between transformational leadership style on employee performance, and to know differences in transformational leadership styles, motivation, and employee performance in the Caturtunggal and Condongcatur sub-districts. The research samples used are 88 people. The data collection technique used is the census method. The analysis technique used is path analysis with the partial least square method using Sobel test and Chi Square test. The results of this research are outlined as follows: 1. The transformational leadership style has a positive and significant effect on the performance of the employees of the Condongcatur and Caturtunggal sub-districts, Sleman Regency, so that the first hypothesis in this study is accepted. 2. Transformational leadership style has a positive and significant effect on the employees performance of Condongcatur and Caturtunggal sub-districts through motivation, so that the second hypothesis in this study is accepted. 3. There is no difference in transformational leadership style, motivation, and employee performance in the Caturtunggal and Condongcatur sub-districts, Sleman Regency, so the third hypothesis in this study is rejected.